PT-symmetric kinks - De Souza Dutra, A. [UNESP]; Dos Santos, V. G.C.S. [UNESP]; Amaro De Faria, A. C. [UNESP] (American Physical Society (APS), 2007)
Some kinks for non-Hermitian quantum field theories in 1+1 dimensions are constructed. A class of models where the soliton energies are stable and real are found. Although these kinks are not Hermitian, they are symmetric under PT transformations. © 2007 The American Physical Society.